1984
DOI: 10.1029/ja089ia09p07467
|View full text |Cite
|
Sign up to set email alerts
|

Multiple correlation between auroral and magnetic pulsations: 2. Determination of electric currents and electric fields around a pulsating auroral patch

Abstract: The multiple correlation method has been applied to the study of concurrent auroral and magnetic pulsations on the basis of videotapes of all‐sky television camera auroral records and induction magnetometer records. The results are (1) the ground magnetic pulsations below pulsating auroras are well represented by a regression model where the magnetic change is expressed as a linear combination of auroral luminosity fluctuations at various parts of the sky, (2) the magnetic variation observed at a single statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…A similar model for auroral pulsating patches was proposed by Oguti and Hayashi [1984] and Oguti [1986]. A three‐dimensional current system is associated with each patch.…”
Section: Discussionmentioning
confidence: 92%
“…A similar model for auroral pulsating patches was proposed by Oguti and Hayashi [1984] and Oguti [1986]. A three‐dimensional current system is associated with each patch.…”
Section: Discussionmentioning
confidence: 92%
“…The pronounced temporal modulations (few seconds to few tens of second periods) are likely caused by groups of closely spaced individual chorus elements (lower band scattering the high-energy primaries), and these distinct patches may also be associated with field-aligned currents [Arnoldy et al, 1982;Oguti and Hayashi, 1984;Fujii et al, 1985;Hosokawa et al, 2010]. Therefore, the strong temporal modulations within distinct patches likely have upward field-aligned currents associated with them and therefore parallel potential drops which would be preventing the secondaries from leaving both the Southern and Northern Hemispheres, if the potential structure is symmetric.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the horizontal convergence or divergence of ionisation due to horizontal drifts and sharp gradients in the ionisation rate, or to sharp gradients in the electric field and hence the horizontal drift, may be important. Oguti and Hayashi (1984) have shown that sharp electric-field gradients are to be expected at the edges of pulsating patches. Another possibility is that we are not measuring true electron density with the EISCAT radar but enhanced scatter due to plasma turbulence (e.g.…”
Section: Applications In the E-regionmentioning
confidence: 99%